2022
DOI: 10.3389/fbioe.2022.792848
|View full text |Cite
|
Sign up to set email alerts
|

Wristwatch PCR: A Versatile and Efficient Genome Walking Strategy

Abstract: Genome walking is a method used to retrieve unknown flanking DNA. Here, we reported wristwatch (WW) PCR, an efficient genome walking technique mediated by WW primers (WWPs). WWPs feature 5′- and 3′-overlap and a heterologous interval. Therefore, a wristwatch-like structure can be formed between WWPs under relatively low temperatures. Each WW-PCR set is composed of three nested (primary, secondary, and tertiary) PCRs individually performed by three WWPs. The WWP is arbitrarily annealed somewhere on the genome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 49 publications
0
33
1
Order By: Relevance
“…In some situations, more than one clear target DNA band appeared (Figure 1). This multiple-band phenomenon is common in randomly primed PCRs and occurs due to the annealing of the walking primers to multiple sites on the unknown flank in the low-stringency cycle (Chang et al, 2018;Wang et al, 2022). At most two major bands appeared in each secondary FPR-PCR in the present study, much fewer than the approximately five bands reported in the other methods (Chang et al, 2018;Wang et al, 2022).…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…In some situations, more than one clear target DNA band appeared (Figure 1). This multiple-band phenomenon is common in randomly primed PCRs and occurs due to the annealing of the walking primers to multiple sites on the unknown flank in the low-stringency cycle (Chang et al, 2018;Wang et al, 2022). At most two major bands appeared in each secondary FPR-PCR in the present study, much fewer than the approximately five bands reported in the other methods (Chang et al, 2018;Wang et al, 2022).…”
Section: Discussioncontrasting
confidence: 52%
“…Additionally, the ability to perform parallel simultaneous experiments provides a further guarantee for the success of FPR-PCR, as at least one FPR-PCR will give a positive outcome. FPR-PCR provides a high success rate similar to those reported for randomly primed PCRs, such as partially overlapping primer-based PCR ( Li et al, 2015 ), stepwise partially overlapping primer-based PCR ( Chang et al, 2018 ), and wristwatch PCR ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations